Mechanical Erosion in a Tropical River Basin in Southeastern Brazil: Chemical Characteristics and Annual Fluvial Transport Mechanisms. (13th December 2012) - Fernandes, Alexandre Martins; Nolasco, Murilo Basso; Hissler, Christophe; Mortatti, Jefferson
Abstract : This study aims to evaluate the mechanical erosion processes that occur in a tropical river basin, located in the São Paulo state, southeastern Brazil, through the chemical characterization of fine suspended sediments and the transport mechanisms near the river mouth, from March 2009 to September 2010. The chemical characterization indicated the predominance of SiO2, Al2 O3, and Fe2 O3 and showed no significant seasonal influences on the major element concentrations, expressed as oxides. The concentration variations observed were related to the mobility of chemical species. The evaluation of the rock-alteration degree indicated that the physical weathering was intense in the drainage basin. The fine suspended sediments charge was influenced by the variation discharges throughout the study period. The solid charge estimate of the surface runoff discharge was four times higher in the rainy season than the dry season. The transport of fine suspended sediments at the Sorocaba River mouth was 55.70 t km −2  a −1, corresponding to a specific physical degradation of 37.88 m Ma −1, a value associated with the mechanical erosion rate that corresponds to the soil thickness reduction in the drainage basin.